Iraq - Financial Sector Review - Nasr, Sahar; Petersen, Arne; Vossen, Jan Van der; Hashad, Nabil; Britton, Richard; Kulaksiz, Sibel; Huitfeld, Erik (World Bank, Washington, DC, 2012)
The link between sound and well-developed financial systems and economic growth is fundamental. Efficient and prudent allocation of resources by the financial system is critical for increasing productivity, boosting economic development, enhancing equality of opportunity, and reducing poverty. The financial sector in Iraq remains underdeveloped and underperforming. The banking system is by far the most important part of the financial system, accounting for over 75 percent of assets and is overwhelmingly state-owned. Non-bank institutions and markets are small and underdeveloped. Access to finance is impeded by a weak financial infrastructure, which needs strengthening in all areas: credit registry, the collateral framework, judicial systems, and accounting and auditing skills. It is also important to keep in view the political context. The difficult security situation imposes costs and constraints, the complex political situation impedes decisive policy action, governance issues linger, and the impact of state intervention continues despite reforms.